A PROGRAM TO IMPROVE THE PHYSICAL QUALITIES OF FEMALE STUDENTS WITH DISABILITIES BASED ON THEIR ABILITY TO MOVE - Berdiyeva, Charos (Журнал иностранных языков и лингвистики, 2023)
The article is focused on the survey of female students with disabilities to improve their physical qualities based on their ability to move.